Gender and poverty in the United States: Evidence from the Survey of Consumer Finances - Patti J. Fisher (PLoS ONE, 2026)
This study examines gender differences in poverty determinants among single-headed households in the United States using data from the 2022 Survey of Consumer Finances. Using logistic regression with decomposition methods, we analyzed 1,383 households (833 female-headed, 550 male-headed) to identify factors associated with living below the federal poverty threshold. Results reveal significant differences in poverty determinants between men and women. Working for an employer, self-employment, education level, and age were negatively associated with poverty, while fair health status and income uncertainty were positively associated with poverty risk. The decomposition analysis found a statistically significant coefficient effect (p < 0.0001), indicating that the impact of independent variables on poverty likelihood differs by gender. Employment showed a marginally significant differential effect (p = 0.068), with working for an employer having a smaller protective effect against poverty for women compared to men. However, no constant effect was detected, suggesting gender differences in poverty result from differential responses to specific determinants rather than gender itself. Female-headed households were more likely to have dependent children (38.3% versus 12.7%) and report poorer health status, while male-headed households had higher average net worth. These findings suggest that gender-neutral poverty reduction strategies may be insufficient, and that targeted interventions, such as affordable childcare support to enhance labor market participation among low-income women, are needed to effectively address gender disparities in poverty rates.